Adaptation of delone and McLean model for ERP system quality evaluation - Vesna Pavković; Dražena Gašpar; Mario Jadrić (Economic Review: Journal of Economics and Business, 2021)
This paper aims to determine whether the DeLone and McLean information system success model (D&M model) can be used to evaluate the quality of Enterprise Resource Planning system (ERP system). The study examines the dimensions of the D&M model, adapted for empirical evaluation of ERP system quality by end-users of ERP systems in enterprises. The quality of ERP systems is measured by comparing answers to questions that serve to determine the degree of quality of each dimension of ERP system quality. The research was conducted on 335 medium and large companies in Bosnia and Herzegovina, for which it has been confirmed in the pilot research to have an ERP system that they have used for more than two years. A survey questionnaire is used to investigate the quality of the ERP system from the perspective of the middle and top management of the companies that use information from the ERP system for decision making. The empirical research has confirmed that the D&M model of information system success, with some adjustments, can be used to investigate the quality of ERP systems. The main limitation of the research is the lack of a database of companies using ERP systems that makes the data collection phase more difficult and more complex. Regardless of this, the proposed model can be used to evaluate the quality of ERP systems, but also some other types of information systems in future research, such as BI and CRM systems
Keywords: M15; M20; 330; ERP system; DeLone and McLeanmodel; ERP system quality; ERP system dimensions